Effect of online training amidst Covid-19 pandemic on maintaining physical and technical level for junior female basketball players - Helmy Moselhy, S. (The International Scientific Journal of Physical Education and Sport Science, 2021)
The world faces Covid-19 pandemic that spread to many countries around the globe. It was declared by the World Health Organization as an international health emergency requiring isolation at home and social distancing, the thing that forced players to abruptly stop their training routines at courts leading to a decline in their physical and technical performance. This study aims at identifying the effect of the online training amidst Covid-19 pandemic on maintaining the physical and technical level for junior female basketball players. The online training program including technical and physical exercises was applied at home for the experimental group (n=10) for (14) weeks, the duration of courts closure due to Covid-19 pandemic, using Zoom and WhatsApp applications. Whereas the control group (n=10) has completely stopped training during the courts closure period. The tests used for pre and post measurements were: Alternate Hand Wall Toss Test, Pushing Medicine Ball "2kg", Standing Board Jump Test, 20-m Sprint Test, Illinois Agility Test, Shooting at Overlapping Rectangles Test, 800-m Run Test, Free Throw test, Layup Test "left and right", and Compound Technical Test. The most prominent results were, the existence of statistically significant differences between experimental and control groups in basketball physical fitness elements, except for agility and cardiorespiratory endurance elements in favor of post measurement for the experimental group. Furthermore, there are statistically significant differences between both experimental and control groups in the technical level, except for free throw skill in favor of the post measurement for the experimental group.